PENGARUH KUALITAS PRODUK, PERSEPSI HARGA, IKLAN, DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN SEPEDA MOTOR YAMAHA DI DEALER YAMAHA AGUNG MOTOR KAJEN KABUPATEN PEKALONGAN - Akas Pandu Pamungkas, 14.05.51.0215 (Students' Journal of Economic and Management, 2018)
This study aims to analyze the effect of product quality, perception of price, advertising, and brand image on the purchase decision of Yamaha motorbike in Yamaha Agung Motor Kajen Dealer in Pekalongan Regency. The population in this study were consumers of Yamaha motorcycles. The instrument used in this study is a questionnaire distributed directly to the research sample as many as 100 respondents. The sampling technique uses purposive sampling. Data analysis techniques used include validity test, reliability test, normality test, multiple linear regression analysis, model testing with F test, test coefficient of determination (R2), and hypothesis testing (t test).The results showed that product quality, price perception, and advertising partially had a significant positive effect on Yamaha motorcycle purchasing decisions, while brand image had a negative and significant influence on the purchase decision of Yamaha motorbikes. Based on the results of multiple linear regression analysis, price perception is the most dominant variable in influencing the purchase decision of Yamaha motorbikes. Keywords: purchasing decisions, product quality, price, advertising, brand image.